Research Progress in Luminescent Rare Earth Complexes - Luo, Xuejuan; Zhong, Yuwei; Chen, Xingying; Jia, Pengkun; Zeng, Yicheng (International Journal of Materials Science and Technology Studies, 2025)
This paper presents a systematic review and synthesis of the field of luminescent rare earth complexes, highlighting landmark research advances achieved over the past decades and offering perspectives on future research priorities and application scenarios for these materials. Luminescent rare earth complexes are poised to continue playing a pivotal role in driving technological innovation and promoting sustainable development on a global scale. Against this backdrop, and drawing on recently published literature and experimental data, this study systematically organizes and summarizes research progress in luminescent rare earth complexes, with the aim of providing a valuable reference for ongoing investigations in this field.